Synthesis of dl-aleprylic acid - Akira Tanaka (Journal of Lipid Research, 1969)
dl-Aleprylic acid [7-(cyclopent-2′-en-1′-yl)-heptanoic acid], a natural constituent of chaulmoogra oil with reputed antileprosy properties, has been synthesized. Electrolysis of a mixture of (cyclopent-2′-en-1′-yl)-acetic acid and methyl monoester of heptanedioic acid in methanol yielded, after saponification of the reaction products, the racemic mixture.